Konstitusionalitas Kekuasaan Presiden Dalam Menetapkan Jumlah Kementerian Negara - Romi; Delfina Gusman (LPPM Universitas Ekasakti, 2026)
Article 15 Number 61 of 2024 is the legality for the President in determining the number of state ministries. On the other hand, Article 17 paragraph (4) of the 1945 Constitution of the Republic of Indonesia delegates that the establishment, amendment, and dissolution of state ministries is regulated in the law, the delegation has implications for the regulation or determination of the number of state ministries stated in the content of the law The results of the research are First, the power of the President in the 1945 Constitution of the Republic of Indonesia in this study is divided into two types, namely: first, the President's power is based on the check and balance mechanism. second, the power of the President is singular, the power of the President is the power of the President regulated in the 1945 Constitution of the Republic of Indonesia, where the power does not 'intersect' with other functions of state power, both in the capacity of the President as the head of government and as the head of state. The President's power is sole within the scope of state ministries in the 1945 Constitution of the Republic of Indonesia only related to the power to appoint and dismiss ministers, it does not include in determining the number of state ministries as mandated by Article 15 Number 61 of 2024. According to the lawmakers, the President's power to determine the number of state ministries is the prerogative of the President.